Effects of changed grazing regimes and habitat fragmentation on Mediterranean grassland birds - Reino, Luís (2010)
In Iberian cereal-steppes, decoupling of payments from current production levels through the Single Farm Payment raised concerns regarding the potential for land abandonment and replacement of sheep by cattle, with eventual negative consequences for declining grassland birds. This study addressed this issue by analysing the responses of five grassland bird species of conservation concern to spatial land use gradients, which are expected to reflect changes potentially associated with the CAP reform. Our results show that both habitat fragmentation and grazing regimes were major drivers of breeding bird densities, though responses to these factors were species-specific. Thekla larks were most abundant in landscapes with small grassland patches and high edge density, whereas calandra larks were abundant only in large expanses of continuous open farmland habitat. Little bustard and short-toed lark densities declined in highly fragmented landscapes, but they appeared to tolerate or even benefit from low to moderate levels of open habitat fragmentation. Corn buntings were little affected by landscape patterns. At the field scale, little bustard and corn bunting densities were highest in fields grazed by cattle, whereas short-toed larks were mostly associated with sheep pastures. Short-toed larks and Thekla larks were most abundant in old fallow fields where cattle was largely absent, whereas corn buntings showed the inverse pattern. These results confirm the view that the same agricultural policies may be favourable for some species of conservation concern but detrimental to others, and so they cannot be assumed to bring uniform conservation benefits.